(untitled) (Fiep Bulletin - online, 2015)
The purpose of this study is to establish the relationship between BMI, socioeconomic status, regular exercise practice and daily physical activity level of children and their parents from private schools of Curitiba-PR. The sample was composed of 45 subjects (15 eight-year-old school children, 15 fathers and 15 mothers). This sample was divided in two groups: sedentary children and their parents (n=24) and active children and their parents (n=21). At first, all subjects’ body mass and stature were assessed, and then the BMI was calculated. A questionnaire was used to assess the socioeconomic status, and the regular exercise practice and habitual physical activity level was determined by using, from all subjects (fathers, mothers and children), a three-day diary (BOUCHARD et al., 1983). Group comparisons were made by one-way ANOVA´s and Pearson moment product was used to verify the relationship among all variables (P<0,05). The correlation results did not show significant difference between father’s physical activity level and the family income (r=0,60), which means that the higher the family income the lower the father’s PAL. In this sample, the fact of being either active or sedentary children is not related to the parents´ physical activity. However, more studies, with large sample, are necessary to investigate this issue.